PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISTEM PERSAMAAN LINEAR DUA VARIABEL SISWA KELAS VIII MTS PP DARUL FATAH - Rinieke Ammelia; Amir Luthfi; Kasman Edi Putra; Astuti; Zulfah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on students’ mathematical problem-solving ability in the topic of System of Linear Equations in Two Variables (SPLDV). The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of two eighth-grade classes at MTs PP Darul Fatah selected through purposive sampling. The research instrument was an essay test, analyzed using the Wilcoxon Signed Rank Test to measure improvement within a single class, the Independent Sample T-Test to compare results between classes, and normalized gain (N-Gain) to assess the effectiveness of the learning model. The Wilcoxon test results showed that 25 students in the experimental class experienced score improvement, while only 9 students in the control class showed the same. The Independent Sample T-Test produced a t-value of 3.245 with a significance level of 0.002 < 0.05, indicating a significant difference between the experimental and control classes. The average N-Gain score in the experimental class was 1.0278 (high and effective category), while in the control class it was 0.2931 (low and ineffective category). Thus, the Problem Based Learning model has been proven to have a significant and effective impact on improving students’ mathematical problem-solving ability.